Effect of nursing intervention on women's knowledge about pregnancy problems and utilization of obstetrics care services in Edu, Kwara State, Nigeria - Umar N. Jibril; Arimiyau A. Sanusi; Abdullahi N. Adamu; Joel O. Aluko; Emmanuel E. Anyebe; Mulikat A. Ibraheem; Moridiyat O.A. Adeyemo; Imam A. Abubakar (Elsevier, 2024)
Purpose: This study assesses the effect of nursing intervention on the knowledge of women about pregnancy-related problems and utilization of obstetrics care services in Edu, Nigeria. Methods: Pre-test post-test control of quasi-experimental design was adopted for the study. Researchers-designed questionnaire was used for data collection and a split-half test was used to determine the reliability of the instrument. One hundred and twenty women were exposed to ten weeks of community-based nursing education intervention sessions, (sixty experimental groups and sixty control groups). Pre-tests administered to sampled women before nursing health education intervention sessions and followed by Post-test. The results were analyzed using mean and standard deviation while the t-test was used to test the hypothesis at an Alpha level of 0.05. Results: The findings showed the positive effect of a nursing health education intervention on the knowledge of women about pregnancy problems with pre-intervention on experimental group mean of 63.33, and post-intervention mean of 72.22 with t-value of 1.26 less than the table value of 1.96. The study further showed a mean score of 35.97 experimental group and 28.33 for the control group with a t-value of 1.64, which shows little effect of intervention on the willingness of women to utilize obstetrics care services in Edu, Nigeria. Conclusion: The study concluded that the nursing health education intervention programme in this study on pregnancy-related problems programmes had a positive effect on the knowledge of women but had no effect on the utilization of OCS by women in Edu Local Government Areas. We recommended that health education programmes should be intensified to improve the knowledge level of women and encourage the use of obstetric care services in the community.